The Welfare State and Higher Education on Their Way Towards Privatisation. Global and Transition Economies’ Perspectives1 - Kwiek, Marek (My University, 2007)
The future of the welfare state in its traditional European forms, and of its services, including public higher education, looks roughly similar all over Europe (exceptions include such small countries of advanced information economies as e.g. Finland). Unfortunately, most lines of argumentation point in the same direction, even though the concepts used may be different. The story gets even more homogenous if we leave the domain of affluent Western democracies which have inherited their welfare provisions from the “Golden age” and pass on to most developing countries and the European transition countries. In this new context, many discussions about welfare futures seem academic: what they shyly predict for affluent democracies is in fact already happening in transition economies; happening in full swing, with almost no other policy options being considered; sometimes with no other options being supported, championed or acclaimed by these very same affluent democracies. There is certainly a lot of social experimentation with respect to welfare going on in the transition countries. It could even be argued that the future directions of welfare transformations in Western democracies are being experimented with to various degrees of success in transition countries; in some areas, like pensions reform with the three-pillar model designed by the World Bank and applied in some Latin American and European transition countries, this intention even happens to be formulated explicitly. Nowadays, as the reduction of the welfare state in general progresses smoothly (and mostly in an unnoticeable manner e.g. through new legislation) in most parts of the world, social contracts with regards to most areas of state benefits and state-funded services may have to be renegotiated, significantly changing their content. In many respects, higher education (in transition countries and elsewhere) seems to be an experimental area and a testing ground on how to reform the public sector in many countries and for many organizations; both higher education, healthcare and pensions systems are being experimented with, both in theory and in practice. The end-products of these experimentations are still largely hard to predict.
Keywords: welfare state; privatization; public sector; postwar social contract; austerity; globalization; state and market; market forces; nation-state; competition; public resources; public services; World Bank; social policy; transition; transition economies; CEE; Central Europe; Eastern Europe; the future of the welfare state; welfare state futures; postcommunism; market economy; open economies; Golden Age; higher education; postcommunist welfare state; postcommunist welfare